Comparison of Coated and Uncoated Trace Minerals on Growth Performance, Tissue Mineral Deposition, and Intestinal Microbiota in Ducks - Yin, Dafei; Zhai, Feng; Lu, Wenbiao; Moss, Amy F.; Kuang, Yinggu; Li, Fangfang; Zhu, Yujing; Zhang, Ruiyang; Zhang, Yong; Zhang, Shuyi (Frontiers in Microbiology, 2022)
Abnormally low or high levels of trace elements in poultry diets may elicit health problems associated with deficiency and toxicity, and impact poultry growth. The optimal supplement pattern of trace mineral also impacts the digestion and absorption in the body. For ducks, the limited knowledge of trace element requirements puzzled duck production. Thus, the objective of this study was to investigate the influence of dietary inclusions of coated and uncoated trace minerals on duck growth performance, tissue mineral deposition, serum antioxidant status, and intestinal microbiota profile. A total of 1,080 14-day-old Cherry Valley male ducks were randomly divided into six dietary treatment groups in a 2 (uncoated or coated trace minerals) × 3 (300, 500, or 1,000 mg/kg supplementation levels) factorial design. Each treatment was replicated 12 times (15 birds per replicate). Coated trace minerals significantly improved average daily gain (p < 0.05), increased Zn, Se, and Fe content of serum, liver, and muscle, increased serum antioxidant enzyme (p < 0.05) and decreased the excreta Fe, Zn, and Cu concentrations. Inclusions of 500 mg/kg of coated trace minerals had a similar effect on serum trace minerals and tissue metal ion deposition as the 1,000 mg/kg inorganic trace minerals. Higher concentrations of Lactobacillus, Sphaerochatea, Butyricimonas, and Enterococcus were found in birds fed with coated trace minerals. In conclusion, diets supplemented with coated trace minerals could reduce the risk of environmental contamination from excreted minerals without affecting performance. Furthermore, coated trace minerals may improve the bioavailability of metal ions and the colonization of probiotic microbiota to protect microbial barriers and maintain gut health.